Positive and Negative Signals in Mast Cell Activation - Bulfone-Paus, Silvia; Nilsson, Gunnar; Draber, Petr; Blank, Ulrich; Levi-Schaffer, Francesca (Trends in immunology, 2017)
Mast cells are powerful immune modulators of the tissue microenvironment. Within seconds of activation, these cells release a variety of preformed biologically active products, followed by a wave of mediator synthesis and secretion. Increasing evidence suggests that an intricate network of inhibitory and activating receptors, specific signaling pathways, and adaptor proteins governs mast cell responsiveness to stimuli. Here, we discuss the biological and clinical relevance of negative and positive signaling modalities that control mast cell activation, with an emphasis on novel FcεRI regulators, immunoglobulin E (IgE)-independent pathways [e.g., Mas-related G protein-coupled receptor X2 (MRGPRX2)], tetraspanins, and the CD300 family of inhibitory and activating receptors.
Keywords: Ganglia, Spinal; signální transdukce; receptory IgE; Receptors, IgE; mastocyty; kationické antimikrobiální peptidy; Receptors, G-Protein-Coupled; Signal Transduction; tetraspaniny; imunomodulace; degranulace buněk; Immunomodulation; neuropeptidy; Nerve Tissue Proteins; Neuropeptides; receptory spřažené s G-proteiny; zvířata; Humans; spinální ganglia; antigen Ki-1; proteiny nervové tkáně; Antimicrobial Cationic Peptides; Ki-1 Antigen; Tetraspanins; Mast Cells; receptory neuropeptidů; Cell Degranulation; Receptors, Neuropeptide; lidé; Animals